2020
DOI: 10.3897/zookeys.926.48671
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Cyrtodactylus (Squamata, Gekkonidae) from Cambodia’s Prey Lang Wildlife Sanctuary

Abstract: Cyrtodactylus phnomchiensissp. nov. is described from Phnom Chi, an isolated mountain in Prey Lang Wildlife Sanctuary, Kampong Thom Province, Cambodia. The new species is recognized by having a unique combination of morphological characters, including snout-vent length 76.1–80.7 mm; paravertebral tubercles 31–36; ventral scales 45–54; enlarged femoral scales 0–8, without pores; enlarged precloacal scales 7–10, bearing pores 4–5 in males, pits 1–7 in females; the posterior border of nuchal loop unbroken and poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Vietnam and extends to adjacent regions in easternmost Cambodia and southeast Laos (Nazarov et al 2012;Nguyen et al 2013;Neang et al 2020;Ostrowski et al 2020;Fig. 9).…”
Section: Cyrtodactylus Irregularis Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Vietnam and extends to adjacent regions in easternmost Cambodia and southeast Laos (Nazarov et al 2012;Nguyen et al 2013;Neang et al 2020;Ostrowski et al 2020;Fig. 9).…”
Section: Cyrtodactylus Irregularis Groupmentioning
confidence: 99%
“…9). The group was previously considered to be a single species, С. irregularis (Smith 1921), until a number of studies demonstrated its unprecedented diversity with 20 new species described within the last 14 years (Nguyen et al 2013;Neang et al 2020;Ostrowski et al 2020). This analysis reveals at least 11 more lineages corresponding to potentially undescribed species and taxonomic investigations on these lineages are currently underway by various authors.…”
Section: Cyrtodactylus Irregularis Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to compare the newly discovered population of Cyrtodactylus sp. from Khanh Hoa Province with other members of the irregularis species group, we generated a 672 base pair segment of the 5'-end of (CO1) which included 29 sequences of 26 species and compared it with the CO1-barcoding dataset from Pauwels et al (2018) and Neang et al (2020). Cyrtodactylus intermedius was used as an outgroup to root the tree based on Wood et al (2012.…”
Section: Genetic Data and Analysesmentioning
confidence: 99%
“…The small inset map shows Vietnam and the location of the area of studies detailed in a larger map (red rectangle). For details on species localities see Pauwels et al (2018); Neang et al (2020); and Ostrowski et al (2020). ed that species within the irregularis group bearing the same habitat preference did not form monophyletic subgroups, but were nested in different places throughout the group's phylogeny.…”
Section: Introductionmentioning
confidence: 99%